Step VEP visual acuity in a pediatric neuro-ophthalmological cohort - Mackay, Alison M (International Journal of Clinical and Experimental Ophthalmology, 2022)
Steady-state VEPs, have been used to estimate visual acuity since the 1970s and allow responses to a range of stimulus sizes to be collected rapidly- with particular utility in infants. However, the assessment of children with cortical visual impairment is a bigger challenge that lead to the development of the Step VEP. Its initial evaluation revealed that accuracy and precision were poorer for pediatric patients than for optically degraded normal adults and that it was not necessarily successful in every child. Statistical models generated the equations: VAO = 0.56 VAStep (r2 = 0.75, F = 60.93, p = 0.000) and VAPL = 0.45 VAStep (r2 = 0.82, F = 156.85, p = 0.000), supported by a recent a systematic review of VA comparisons showing that recognition VA (optotypes) agrees more closely than discrimination VA (PL) with VEP VA. In combination, Step VEPS and subjective tests allowed complete assessment in 96% of patients, with incomplete Step VEPS much more likely to be partially successful than not, and more likely to be partially successful than incomplete subjective tests. This supports the rationale that Step VEPs maintain attention by limiting the time spent stimulating away from an individual’s threshold of spatial resolution. For the small number of patients in whom VA cannot be estimated, alternative stimuli and methods of presentation are proposed.